Effect of different winterhardiness cultivars on alfalfa’s yield grown in Northern oasis of Mendoza - Rebora, Cecilia; Barros, Ariel; Ibarguren, Leandra; Bertona, Alejandra; Antonini, Carlos; Arenas, Fernando (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2015)
Alfalfa is the most important forage grown in Mendoza. It represents 4.1% of the cultivated area in the province and the 60% of the forages grown in it. Environmental conditions determine the fall dormancy group to be selected. Mendoza does not belong to the National Cultivars Evaluation Net; and there is no local information that allow us to select the correct cultivar according to fall dormancy (FD). The objectives of this study were: identify the fall dormancy group or groups of alfalfa that have the higher yields in North oasis in Mendoza, determine the number of cuts per year per cultivar, forage quality, and cultivar persistance. The study was conducted at the FCA experimental farm, located 33º00’30" S and 68º52’32" W. A cultivar representative of each fall dormancy group from 6 to 10 was evaluated, during two growing seasons (2012-2013 and 2013-2014). No significant differences were found in number of cuts/year, anual dry matter production, leaves/stems ratio, and persistance between groups of fall dormancy.